UTILIZATION OF 100% WASTE OIL IN DELTA E EMULSION EXPLOSIVE MIXTURE FOR COAL OPEN MINE: PEMANFAATAN WASTE OIL 100% DALAM CAMPURAN BAHAN PELEDAK EMULSION DELTA E UNTUK TAMBANG TERBUKA BATUBARA - Santika Pradhana; Shenny Linggasari; Relinda Este; Dicky Ervando (INTAN Jurnal Penelitian Tambang, 2023)
The limitation of coal reserves poses a challenge for the mining industry to optimize coal extraction. Innovations are constantly being sought to enhance efficient productivity while considering environmental sustainability. The innovation of utilizing waste oil up to 100% as a substitute for fuel in the emulsion production process is expected to improve environmental quality without compromising blasting quality. The results showed that the fragment size (P80) in the 85% waste oil trial was 227.8 mm, while in the 100% waste oil trial, it was 325.1 mm. The recovery rate in the 85% waste oil trial location was 95.7%, whereas in the 100% waste oil trial location, it was 95.9%. The measured VoD in the 85% waste oil trial was 4636 m/s, while in the 100% waste oil trial, it was 4632 m/s. VOD numbers show that explosives performed well with no decrease in quality. No fumes appearance shows proper chemical reaction within explosives detonation. 100% waste oil usage is proven to deliver optimum blast results, hence providing efficiency on fuel saving and delivering additional value on recycled hazardous waste produced from mining activity.